Harmful Algal Blooms: Identifying Effective Adaptive Actions Used in Fishery-Dependent Communities in Response to a Protracted Event - Moore, Kathleen M.; Allison, Edward H.; Dreyer, Stacia J.; Ekstrom, Julia A.; Jardine, Sunny L.; Klinger, Terrie; Moore, Stephanie K.; Norman, Karma C. (Frontiers in Marine Science, 2020)
The ‘blob’ of anomalously warm surface water that persisted in the North Pacific Ocean from 2013-2016 resulted in a massive harmful algal bloom (HAB) of Pseudo-nitzschia along the entire U.S. West Coast. The bloom produced record-breaking concentrations of domoic acid, a marine neurotoxin, that contaminated seafood and necessitated fisheries harvest closures beginning in May 2015. The subsequent closures were unprecedented in length and geographic extent, generating an economic shock for fishing communities. We sought to identify effective adaptive actions used in fishery-dependent communities in response to this event. Using survey data collected across 16 fishing communities following the 2015 HAB event, we empirically identified factors affecting an individual’s: 1) absolute magnitude of income loss, 2) likelihood of income loss recovery, and 3) severity of emotional stress. Our findings indicate that individuals who suffered greater absolute income losses were exposed to longer fisheries closures, more dependent on shellfish as a source of income, and employed in the fishing industry. Income diversification was an effective strategy for reducing and/or recovering HAB related income losses. Advertising was also found to be an effective income recovery strategy, but for fishers it was associated with increased emotional stress. If increasing the adaptive capacity of fishery-dependent coastal communities to HAB events is a policy goal, then costs to adaptive action such as emotional stress, limited access to alternate fisheries, new fishing gear, a lack of alternate job skills or access to job networks, and a lack of advertising know-how will need to be addressed.